Achievement and key success factors of regional tourism in Malaysia: an analysis from 2008-2020 era - Wan Suzita Wan Ibrahim; Habibah Ahmad; Fauzunnasirah Fazil; Mohamad Kazar Razali; Nor-Ina Kanyo; Kiki Rizki Makiya (ResearchTrentz, 2022)
Regional tourism is one of the approaches often utilized to ensure a balance of economic growth, distribution of tourist flows and tourism development. In Malaysia, regional tourism can be traced date back to the third Malaysia Plan. However, with the economic development corridors taking place more will is argued provincial tourism achievement level in Malaysia. This article aims to analyze how regional tourism has been packaged by the tourism providers and regional tourism stakeholders such as ECER, NCER and the Iskandar Malaysia (IM) since 2008 until 2016 year. The research method was based on content analyzed in the late 2008 until 2016 year. The findings show that unpacking of the regional tourism images are due to another the commitment of the stakeholders in realizing their touristic assets, tourism attraction, regional capacity and local involvement in working closely with the states involved. While there are potential in regional tourism development, a strong image should be the key to cooperation among the stakeholders of the country’s regional development corridors.